Recent Trends in Criminal Law Reform - Létourneau, Gilles; Zimmerman, Suzan (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1992)
A review of recent legislative, judicial and administrative reforms in criminal matters shows an increased thrust toward greater fairness and efficiency of the criminal justice system. This has materialized in an increased protection of individual rights, a renewed interest in diversion and alternative dispute resolution mechanisms, a streamlining of the process through court reform, caseflow management and a simplification of the criminal procedure and a greater openness to the use of new technology. Although contradictory at first sight, efficiency and fairness are two necessary and complementary attributes of the criminal justice system.